Behavioral and psychological features in girls and women with triple‐X syndrome. Issue 11 (2nd August 2018) - Freilinger, Petra; Kliegel, David; Hänig, Susann; Oehl‐Jaschkowitz, Barbara; Henn, Wolfram; Meyer, Jobst
Abstract : Triple‐X syndrome is a common sex chromosome aneuploidy, which appears in 1 out of 1, 000 females. The aim of our study was to describe the behavioral features of a large group of girls and women with triple‐X in comparison to a control group. A total of 72 subjects with triple‐X and 69 subjects of an age‐matched control group were included. Psychological and behavioral questionnaires were allocated to three age groups, representing a range of ages from young childhood to adulthood. Regarding the females between 4 and 7 years of age, we found significant differences for social problems, attention problems, and school performance. For the age group 8–17 years, we found larger significant differences for the majority of the scales listed in the child behavior checklist. The most significant differences ( p < .001) were from total behavior problems, internalizing problems, and four other scales. Young females with triple‐X have significantly lower general self‐esteem, especially concerning school and family. In the adults, there were significant differences concerning psychological symptoms and distress, with higher scores in the triple‐X subjects. Regardless, their mean scores were still in the normal range. We did not find clinical evidence for more than 50% of the triple‐X females in any age group, indicating that approximately half of them do not have behavioral problems, and that more than 60% do not differ in their competence from the control group. However, our findings suggest that triple‐X influences mental health and the overall well‐being of the individuals across their whole life spans.